The Effectiveness of Repeated Reading and Supported Cloze Procedure to Improve Beginning Reading Skills in Elementary School Slow Learner Students - Sofianti, Rahma Elok; Andriani, Fitri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Literacy plays a very important role in the academic performance and overall development of elementary school students. However, many elementary school age children experience problems in reading, including fluency, accuracy and reading comprehension. This affects the learning process and causes poor academic results. The initial reading ability of 4th grade elementary school slow learner students at MI Salafiyah Mahbubiyah still has not received special treatment to improve their reading ability. Improving initial reading skills in slow learner students must be done in the right way, one of which is repeated reading and supported cloze procedures. To overcome this problem, the intervention was carried out using the repeated reading method and supported cloze procedure. The aim of this research is to see the effectiveness of repeated reading and supported cloze procedures to improve the beginning reading abilities of slow learner students in grade 4 of elementary school. This intervention aims to improve early reading skills in elementary school children who experience slow learning. This research uses a single case experimental design, where the subjects are 4th grade elementary school students. The development of the subject's reading ability was measured using Gickling and Armstrong's checklist, namely Reading Proficiency and Error Checklists. The results of the research show that there is a difference after being given the repeated reading and supported cloze procedure technique and before being given the repeated reading and supported cloze procedure on the subject. This means that (Ha) is accepted and (Ho) is rejected. So, it can be concluded that the repeated reading and supported cloze procedure is effective in improving the initial reading skills of slow learner students in grade 4 of elementary school.